Research in Health Care (Advancements in Homeopathic Research, 2022)
Scientific research plays a very important role in our efforts to maintain health and combating diseases. Research helps us create new knowledge and develop proper tools for the use of existing knowledge. Not only does it enable health care providers to diagnose and treat diseases, research also provides evidence for policies and decisions on health and development.
Keywords: Research; Methodology; research topic; Report Writing; Literature review